Curcumin and piperine supplementation of obese mice under caloric restriction modulates body fat and interleukin-1β - Miyazawa, Taiki; Nakagawa, Kiyotaka; Kim, Sharon H.; Thomas, Michael J.; Paul, Ligi; Zingg, Jean-Marc; Dolnikowski, Gregory G.; Roberts, Susan B.; Kimura, Fumiko; Miyazawa, Teruo; Azzi, Angelo; Meydani, Mohsen (Nutrition & metabolism, 2018)
Background Dietary bioactive compounds capable of improving metabolic profiles would be of great value, especially for overweight individuals undergoing a caloric restriction (CR) regimen. Curcumin (Cur), a possible anti-obesity compound, and piperine (Pip), a plausible enhancer of Cur’s bioavailability and efficacy, may be candidate agents for controlling body fat, metabolism and low grade inflammation. Methods 47 eight-week-old male C57BL/6 mice were fed a high fat diet (HFD) for 23 weeks to induce obesity. Then, mice were divided into 5 groups. Group 1 continued on HFD ad libitum. The other 4 groups underwent CR (reduced 10% HFD intake for 10 weeks, 20% for 20 weeks) with Cur, Pip, Cur + Pip or none of these. Percent body fat, plasma inflammatory markers associated with obesity (interferon (IFN)-γ, interleukin (IL)-10, IL-12 p70, IL-1β, IL-6 and KC/GRO), plasma Cur metabolites and liver telomere length were measured. Results Compared to the other groups, obese mice who underwent CR and received Cur + Pip in their diet lost more fat and had significantly lower IL-1β and KC/GRO. Tandem mass spectrometry analysis of plasma from obese mice under CR showed no difference in Cur metabolite levels between groups supplemented with Cur alone or combined with Pip. However, plasma IL-1β levels were inversely correlated with curcumin glucuronide. Minor modulation of telomere length were observed. Conclusions It is plausible that supplementing the high fat diet of CR mice with Cur + Pip may increase loss of body fat and suppresses HFD induced inflammation. Combination of Cur and Pip has potential to enhance CR effects for the prevention of metabolic syndrome.